A Palpation-based and Fluoroscopy-independent Percutaneous Insertion Technique for Medullary Iliac Crest External Fixation Schanz Pins. Issue 1 (March 2016) - Cai, Hong-Min; Li, Hong-Jun; Liu, You-Wen; Wu, Xue-Jian; Ding, Qiang; Zhang, Chuan; Gao, Shu-Tu; Li, Wu-Yin
Abstract : Iliac crest external fixation Schanz pins are usually difficult to be reliably and accurately inserted in the cancellous bone between the iliac cortical tables, which consequently makes this kind of pelvic external fixation often less biomechanically durable than that with supra-acetabular Schanz pins. This report describes a palpation-based fluoroscopy-independent percutaneous insertion technique for medullary iliac crest Schanz pins. This technique can assure the iliac crest Schanz pins to be exactly intraosseous and insert them to an extra depth, providing ample bone engagement and a resultant durable external fixation.